A SYSTEMATIC REVIEW OF RAPID ACCESS MODELS OF CARE AND THEIR EFFECTS ON DELAYS IN EMERGENCY DEPARTMENTS. Issue 6 (19th May 2015) - Evans, Bridie Angela; Porter, Alison; Gammon, Becky; Mayes, Robert Harris; Poulden, Mark; Rees, Nigel; Snooks, Helen; Toghill, Alun; Wells, Bridget; Whitfield, Richard
Abstract : Background: Pressure on emergency departments (EDs) sometimes results in handover delays for patients who arrive in ambulances, leading to operational disruption to the ambulance service and ED, and poorer patient experience. Some EDs have adopted models of care to provide rapid access for emergency patients to senior clinical staff. Methods: We carried out a systematic review of studies describing the operation of a senior clinician-led rapid assessment team in an ED whose purpose was to streamline receiving, treating and discharging patients. We examined research papers published in English 2004–2014, searching eight electronic databases. We used a pre-defined data extraction framework and assessed papers for quality. We used narrative synthesis to analyse and synthesise the data on the characteristics of these models and their impact on patient flow. Results: We identified 628 potentially eligible studies, of which 13 met the inclusion criteria for the review. Most were uncontrolled before and after studies (n=8); two were randomised controlled trials and two were controlled studies. The majority of models shared common characteristics, in addition to being led by senior clinicians: the patient was initially seen by a triage nurse, assessment and treatment occurred simultaneously with triage or followed quickly, and assessment and triage took place within a designated area of the ED. A wide range of outcome measures was collected. All studies which described effects on waiting times reported a reduction, generally across all patient groups. Seven studies reported that patients treated under the model spent less time in the ED between registration and discharge (up to 54% less in one study), with a range of impacts noted on other ED patients. Five studies reported that fewer patients left the ED without being seen. Five studies reported positive feedback from staff. Conclusions: The review suggests that rapid access models in the ED may have benefits for patients, though evidence is still limited.